Subject and partner satisfaction with lip and perioral enhancement using flexible hyaluronic acid fillers. (1st February 2021) - Bertucci, Vince; Nikolis, Andreas; Solish, Nowell; Lane, Vanessa; Hicks, Jessica
Abstract: Background: The injection of hyaluronic acid (HA) dermal fillers is a popular minimally invasive approach to improve lip volume and contour, and with improved techniques has gained popularity because full lips are often associated with beauty and youth. Patient satisfaction is a key driver for successful aesthetic procedures, influencing individual treatment plans and future recommendations. Objective: To evaluate subject and partner satisfaction with the hyaluronic acid (HA) dermal filler HARK for lip enhancement at 8 weeks after the last treatment. Methods & materials: Subjects in this open‐label study all received HARK in the lips, and an additional group also received HARR and/or HARD in nasolabial folds (NLFs) and marionette lines (MLs). Satisfaction was assessed at Weeks 4 and 8 after the last treatment using questionnaires (FACE‐Q™ [subjects] and KISSABILITY [subjects and partners]). Results: Nineteen subjects received HARK only; 40 also received HARR and/or HARD . Subjects reported a high level of satisfaction with their lips following treatment. Increases from baseline in the mean total satisfaction score were statistically significant at Weeks 4 and 8 ( P ≤ .001). Most subjects (≥89%) reported satisfaction on all FACE‐Q questions at Week 8. Both subjects and partners were satisfied with the kissability, appearance, and natural look and feel of the post‐treatment results. Conclusion: This study demonstrated that HARK resulted in lip enhancement with high levels of subject and partner satisfaction, when used alone or in combination with HARR / HARD in NLFs and MLs.